EFFECT OF EDUCATIONAL INTERVENTION ON PERCEPTIONS OF HPV VACCINATION AMONG UNDERGRADUATE FEMALE STUDENTS - Hameed, Shahul; K, Chethana; Khan, Asif (Universitas Airlangga, 2024)
Introduction: India leads the world in terms of the prevalence of cervical cancer. If the HPV vaccine is administered before to first sexual contact, the potential degree of protection is approximately 70%. Aims: To investigate the impact of an educational intervention on perception among undergraduate female students. Methodology: Quasi-experimental design without control groups -One group pretest and post-test study was conducted in a tertiary health care center, among undergraduate female students of Medical, Nursing and Physiotherapy colleges. The study comprised 427 students. Perception of cervical cancer and practice of HPV Vaccination was assessed using a semi-structured questionnaire before giving educational intervention. After a gap of 4 weeks of educational intervention, a post-test was done. Results: data was collected using a semi structured questionnaire before and after intervention and it was found that 93% of the study population who had not had the HPV vaccination (406) were willing to do so in the future, and 90.4% of the entire study population (427) were willing to advise others to obtain the cervical cancer vaccine. Following an educational intervention, 2.8% of pupils received vaccinations in 4 weeks. Conclusion: In this study, medical and paramedical college students who received an educational intervention showed increased knowledge and a shift in behavior, including a willingness to get immunized. Thus, these initiatives can be promoted among female undergraduate students at all colleges, which will enhance their use of the HPV vaccine to prevent cervical cancer